FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBELIAN HANDPHONE PADA MAHASISWA - Tety Asnawi (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
Increasing number of students at the University of Batanghari in the purchase of mobile phones, given its function as a channel of communication in the era of globalization. To know the utilities and student interest in the use of mobile phones are basically a portable cellular phone and a personal item of course people who buy are high and the level of activity needed or wanted people in everyday life. While a student on its obligations or duties to learn and explore the science in general, so it would be the opposite of the personal mobile phone functions that used by the student. This study aims to determine the factors that cause the number of students at the University of Batanghari in the purchase of mobile phones.The results showed that the actor-factors that influence students to buy mobile phones because of the weight of portable, completeness menu, product design, wide-screen monitor and a brandKey Word: mobile phones